The Dance of the Spinning Top (Global Journal of Science Frontier Research, 2016)
Abstract not found
Keywords: Theory of Dynamic Interactions; interaction; inertial field; velocity field; torque; orbiting; angular momentum; angular speed; spinning top; planets